Childhood neurodevelopmental difficulties and risk of adolescent depression: the role of irritability. (25th March 2019) - Eyre, Olga; Hughes, Rachael A.; Thapar, Ajay K.; Leibenluft, Ellen; Stringaris, Argyris; Davey Smith, George; Stergiakouli, Evie; Collishaw, Stephan; Thapar, Anita
Abstract : Background: Children with neurodevelopmental disorders are at increased risk of developing depression. Irritability predicts depression in the general population and is common in children with neurodevelopmental disorders. Thus, it is possible that irritability in children with neurodevelopmental disorders contributes to the link with later depression. This study aimed to (a) examine the association between childhood neurodevelopmental difficulties and adolescent depression and (b) test whether irritability explains this association. Methods: Children with any neurodevelopmental difficulty at the age of 7–9 ( n = 1, 697) and a selected, comparison group without any neurodevelopmental difficulty ( n = 3, 177) were identified from a prospective, UK population‐based cohort, the Avon Longitudinal Study of Parents and Children. Neurodevelopmental difficulties were defined as a score in the bottom 5% of the sample on at least one measure of cognitive ability, communication, autism spectrum symptoms, attention‐deficit/hyperactivity symptoms, reading or motor coordination. The Development and Well‐Being Assessment measured parent‐reported child irritability at the age of 7, parent‐reported adolescent depression at the age of 10 and 13, and self‐reported depression at the age of 15. Depression measures were combined, deriving an outcome of major depressive disorder (MDD) in adolescence. Logistic regression examined the association between childhood neurodevelopmental difficulties and adolescent MDD, controlling for gender. Path analysis estimated the proportion of this association explained by irritability. Analyses were repeated for individual neurodevelopmental problems. Results: Childhood neurodevelopmental difficulties were associated with adolescent MDD (OR = 2.11, 95% CI = 1.24, 3.60, p = .006). Childhood irritability statistically accounted for 42% of this association. On examining each neurodevelopmental difficulty separately, autistic, communication and ADHD problems were each associated with depression, with irritability explaining 29%–51% of these links. Conclusions: Childhood irritability appears to be a key contributor to the link between childhood neurodevelopmental difficulties and adolescent MDD. High rates of irritability in children with autistic and ADHD difficulties may explain elevated rates of depression in the neurodevelopmental group.